ARUNIKA - Simangunsong, Daniel Pedro; Sumerjana, Ketut; Laksmi, Desak Made Suarti (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
Based on the experience, the composer will also create a musical composition entitled Arunika. Arunika is the phenomenon of the emergence of the tip of the sun above the eastern horizon, or this event is often called the sunrise process. Arunika is a word derived from Sanskrit. Sanskrit itself is a member of the Indo-European language family and is considered one of the oldest and most well-known languages among linguists. Sanskrit is a perfect language, an antonym of vernacular or prakrit, often used for religious or scientific purposes. Sanskrit is one of the official languages used in India today, because it is closely related to Hinduism and Buddhism. In India itself, Sanskrit is commonly used in several Hindu religious ceremonies and other major national celebrations. This language is a special language for Indian society, this is because it is a marker of differences in social status so it is only taught to upper classes or castes. The use of Sanskrit has developed into a specific symbol and language not only in India but also in several countries. The word Arunika became the title of the work to reflect a personal experience, namely vision problems, where his eyes became dark and he could not move. The problems experienced by cultivators have a big impact on the path of dreams and the future they have envisioned. The impact of this problem made the cultivator decide on his dream. Arunika herself had a huge influence in the process of creating this work. This work was born from a process of self-healing and recovery accompanied by the environment.